Formulasi dan Uji Efektivitas Sabun Padat dari Ekstrak Etanol Daun Kopasanda (Chromolaena odorata L.) terhadap Bakteri Staphylococcus epidermidis - Hafizhatul Abadi; Hanafis Sastra Winata; Adek Chan; Faadhilah Yusa Simbolon (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Siam Weed leaf plants contain high levels of flavonoids and tannins. These compounds provide antibacterial potential. This study aims to formulate solid soap dosage form of ethanol extract of Siam weed leaves and test the antibacterial activity of it against the growth of Staphylococcus epidermidis bacteria. This is experimental research. Making the extract phytochemical screening test. Evaluation of the dosage form was done by organoleptic tests, homogeneity, pH, foam height, moisture content, irritation, stability, and antibacterial activity tests using the well method. The results showed that solid bath soap dosage form from the ethanol extract of siam weed leaves could be formulated into soap dosage form which had a pH in the range of 9.2 – 9.8, high foam that was stable and did not cause irritation to the skin of volunteers and tested for antibacterial activity on bacteria. Staphylococcus epidermidis with a concentration of 10% 8.84 mm, 15% concentration 10.56 mm and 20% concentration 12.11 mm. The conclusion showed that solid soap dosage form of ethanol extract of Siam weed leaves (Chromolaena odorata L.) could be formulated and fulfilled the requirements after being evaluated and the antibacterial effectiveness of Staphylococcus epidermidis was the best at a concentration of 20% (strong).